Some Ecological, Clinical and Epidemiological Characterisics of the Tick-Borne Encephalitis Incidence in Irkutsk (1995 - 2015) - O. V. Mel'nikova; E. I. Andaev; A. Ya. Nikitin (Эпидемиология и вакцинопрофилактика, 2017)
The results of archive data analysis of the tick-borne encephalitis (TBE) cases in Irkutsk during 1995 - 2015, got from Irkutsk Regional Center for hygiene and epidemiological surveillance, are shown. During the examined period the percent of severe forms and lethal outcomes of the disease have risen. The severe forms came more often at the very beginning and at peak of ticks’ activity season. The number of alimentary TBE cases, illness of anti-TBE vaccinated persons and persons with professional risk of infection have increased in Pribaikalie during 1995 - 2015. The recurring TBE cases have been also recorded.